UNGKAPAN PENYESALAN AKIBAT PERILAKU MENYIMPANG REMAJA PUTRI DALAM KARYA SENI LUKIS KONTEMPORER - Drs. Yasrul Sami, S.Sn., M.Sn., YULI YANTI, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2018)
The purpose of this final work is to visualize the expression of female teenage regret in the phenomenon of promiscuity among young women. Some supporting theories in the creation of this work include: adolescent theory, theories of deviant behavior, the theory of art, contemporary theory.The method of creating artwork, using five stages of preparation stage, elaboration stage, synthesis stage, stage of concept realization and completion stage. the last one, the exhibition, the painting that has been made. In making this work, use acrylic paint on canvas with brush technique and use the appropriate color with the object. The style used is Realist style.Ten works are made telling about a teenager's remorse because of the deviant behavior done, especiall young women. Because women are equated with very beautiful glass plates, if the plate falls, then the beauty and value of its function will be lost. The deviation is influenced by family factors, and environmental factors.Keywords: The deviant behavior of young women, painting, contemporary.